Training volume and previous injury as associated factors for running-related injuries by race distance: A cross-sectional study - Besomi, M.; Leppe, J.; Mauri-Stecca, M. V.; Hooper, T. L.; Sizer, P. S. (Journal of Human Sport & Exercise, 2019)
Objective: This study aims to determine the relationship between weekly pre-competition running volume and the presence of running-related injuries (RRIs) by race distance. Methods: An online questionnaire was sent to 25,000 participants, 14 days following the running event. The questionnaire included the presence and topography of RRIs, previous injury in the last 12 months, running experience, training, and sociodemographic characteristics. Univariate and multivariable binomial regression was used to analyse the crude and adjusted relationship of RRI and training volumes. Results: 4380 surveys were analysed (10km, n=1316; 21km, n= 2168; 42km, n=896). The median age was 36 years. Previous injury was reported by 51.8% of the respondents. Median training volume in the previous month was 15 km/week (IQR 6-24), 30 km/week (IQR 15-40) and 45 km/week (IQR 30-60), for the 10km, 21km, and 42km distances, respectively. During the race, 14.1% reported a RRI, with 43.1% located at the knee. The multivariable analysis showed previous injury and distance as the main associated factors, whereas weekly training volume, age, and previous participation were protective. Conclusion: Race is an inciting event for developing a RRI. Running race distance is an important factor itself and should be incorporated with other modifiable risk factors in current injury models.